THE RELATIONSHIP BETWEEN WORKLOAD AND MOTIVATION WITH HEALTH WORKER’S PERFORMANCE IN COMMUNICABLE DISEASE PROGRAM IN PRIMARY HEALTH CENTRE IN EAST KOLAKA DISTRICT: Workload and Motivation Health Worker - Said, Muhamad; Saafi, La Ode; Sunarsih (Universitas Mandala Waluya Kendari, 2020)
Background: The incidence of infectious diseases in the world, Indonesia and provinces is still relatively high. Based on WHO data (2017), the top ten diseases that cause death are under 5 years of age, including HIV / AIDS 4%, diarrhea 18%, measles 1%, malaria 8%, pneumonia 16%, premature 12%, birth asphyxia 9%. , neonatal sepsis 6%, congenital abnormalities 4%, and accident 3%. In Indonesia, the incidence of infectious diseases is still high and some have experienced an increase in cases from the previous year. The data from the East Kolaka Health Service Profile shows that Accute Respiratory Infection (ARI) has increased by 55%, the number of sufferers is 84, while diarrheal disease has increased by 24%, the number of sufferers is 839, and TB disease has increased by 65% The number of patients 129. Methods: This type of research is a cross sectional study. The population of this study were all programmers in the working area of ??the East Kolaka Health Service as many as 48 programmers. The sampling technique was carried out by simple random sampling using the Lemeshow formula. Data were collected through a questionnaire and then analyzed using the Chi Square test. Result: The results showed that chi square of motivation = 5.773 and workload = 8,644. They chi squar etable is 3,841 at ? = 5% and df = 1. It means that chi square value> chi square table. Conclusion: There was a relationship between motivation, and workload with performance of officers in East Kolaka Regency.